ANALISIS YURIDIS TERHADAP PRAKTIK PENAHANAN IJAZAH DALAM HUBUNGAN KERJA DI INDONESIA - Syaharani, Nabilah; Fitrianto, Bambang; Nurdiana, Citra; Saputra, Defri Dwi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The practice of withholding diplomas by employers within employment relationships in Indonesia has become a controversial phenomenon, despite lacking any legal legitimacy. This study aims to analyze this practice from the perspectives of labor law and human rights, as well as its implications for workers. The research employs a normative juridical method, using a statute approach and conceptual approach to examine relevant legislation and legal doctrines. The findings reveal that withholding diplomas violates Article 169 of Law Number 13 of 2003 on Manpower and the principles of human rights as stipulated in Law Number 39 of 1999, as it restricts workers’ rights to freely pursue employment and maintain possession of their personal documents. Contractual clauses that permit diploma retention contradict the principle of freedom of contract and may be deemed null and void. The implications of this practice include industrial power imbalances, psychological distress, and restricted labor mobility. The study recommends legislative revisions to explicitly prohibit diploma withholding, stricter supervision by labor authorities, and increased stakeholder education. These findings contribute to the broader discourse on labor law and the protection of workers’ rights in Indonesia.